Diagnostic efficiency of methylene blue and lugol's iodine double staining method in oral leukoplakia in detecting dysplasia - Dheeraj Sharma; Aravinda Konidena; Alpna Sharma (Wolters Kluwer Medknow Publications, 2021)
Objectives: Early detection of dysplasia in oral potentially malignant disorders (PMD) might facilitate screening for possible subsequent malignant transformation. Vital staining is a non-invasive clinical adjunct used for determining the biopsy site, which facilitates early detection of dysplastic changes in PMD. Some authors suggested that double staining method has superior results over staining with a single dye. Aim: The aim of the study was to evaluate the accuracy of in vivo staining with methylene blue (MB) and Lugol's iodine (LI) double staining method in comparison with MB staining alone. Materials and Methods: Fifty patients of oral leukoplakia were recruited for the study. After obtaining written informed consent from the patients, the lesions were stained consecutively with 5% MB and 3% LI. The pattern of dye retention of MB alone, followed by MB and LI was noted. Incisional biopsy from the lesion was taken based on the retention of MB and the absence of staining of LI or by clinical judgement in case both stains were not retained. The clinical uptake of the stains was correlated with the degree of dysplasia on histopathological examination. Results: Out of 50 subjects, MB was retained in 47 cases (94%), while 3 cases (6%) failed to retain the dye. However, out of 47 cases, 20 cases had dark blue stain and were considered as MB positive, while the rest 27 cases had pale blue stain and were considered to be negative for MB staining. The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and diagnostic accuracy (DA) of MB staining were 57.82%, 100%, 100%, 26.53% and 46%, respectively. After applying both stains, i.e., double staining method, the outline of the lesion was better defined. Out of 50 PMD cases, 3 patients retained only LI and showed no dysplasia. Out of 47 cases which showed dysplasia, 27 cases showed pale blue retention of MB (-) and also were negative for LI. The rest 20 cases were positive for MB but negative for LI. The sensitivity, specificity, PPV and NPV with double staining technique were 100%. Conclusion: The accuracy and reliability of double staining method was superior to MB staining. Clinical Relevance: Increased accuracy of double staining method aids in better detection of dysplasia and is of great help to the clinician in deciding the nature of PMD in question.